(untitled) (Research, Society and Development, 2022)
This review aimed at assessing the evidence-based literature on the health-related quality of life of Brazilian Basic Education students. A search was carried out in the Virtual Health Library (VHL) databases, which include LILACS, MEDLINE, MEDCARIB, PAHO/WHO, PAHO and WHOLIS; EBSCO and SciELO from January 2010 to July 2020. In order to carry out this search, the following combination of terms was used: ‘Health-related Quality of Life’ AND ‘Students’ OR ‘Schoolchildren’ AND ‘Basic Education’ OR “Elementary Education’ AND ‘Health-related quality of life’ AND ‘Students’ AND ‘Basic Education’. Original studies written in Portuguese and English that had evaluated the health-related quality of life of Elementary and High School students were included. Eight studies met the inclusion criteria, 75% out of them had been carried out in the last 5 years with students aged between 7 and 22 years; thus, a total of 5.507 students participated in the present study. The instruments to assess the health-related quality of life of schoolchildren mainly included PedsQL 4.0 and KIDSCREEN 27. The male students who used to practice sports and with normal weight showed the best scores in the domains and general self-perceived quality of life, when compared to overweight or obese female students, non-practitioners of sports. In conclusion, the health-related quality of life of Brazilian Basic Education students is influenced by sex, lifestyle and nutritional status.